1982
DOI: 10.1128/jvi.44.3.958-962.1982
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the simian virus 40 maturation pathway after butyrate-induced hyperacetylation of histones

Abstract: The role of histone acetylation in the replication and maturation pathways of simian virus 40 was assessed. Histones were hyperacetylated by briefly exposing infected cells to sodium butyrate. Viral DNA in cells exposed to butyrate was found to reenter replication to a greater extent and mature to the previrion form to a lesser extent than viral DNA in control cells. Previrions formed in the presence of butyrate had altered sedimentation properties. These data suggest that increased acetylation of histones is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The fact that the HDAC inhibitors also cause a reduction in the size of the pool of replicating SV40 minichromosomes at late times suggests that HDAC activity may play a role in determining the biological fate of newly replicated SV40 minichromosomes. This suggestion that the fate of newly replicated SV40 minichromosomes may be determined in part by HDAC function is consistent with previous work which showed that treatment of SV40 infected cells late in infection with NaBu reduced the fraction of newly replicated minichromosomes which became committed to the encapsidation pathway [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The fact that the HDAC inhibitors also cause a reduction in the size of the pool of replicating SV40 minichromosomes at late times suggests that HDAC activity may play a role in determining the biological fate of newly replicated SV40 minichromosomes. This suggestion that the fate of newly replicated SV40 minichromosomes may be determined in part by HDAC function is consistent with previous work which showed that treatment of SV40 infected cells late in infection with NaBu reduced the fraction of newly replicated minichromosomes which became committed to the encapsidation pathway [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Butyrate has been reported to exert additional cytostatic effects such as G2/M blockage and antiviral activity against RNA viruses (12,20,52,53,63). We have not examined the possible differences in chromatin structure between large and small DNA viruses in the presence and absence of butyrate to study the potential butyrate-mediated alterations of chromatin structure (33,58) that might contribute to the observed differences in replication patterns among DNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Since cellular DNA and viral replication can be inhibited by butyrate (8,11) we chose nonreplicating recombinant plasaids (12) for our studies.…”
Section: Introductionmentioning
confidence: 99%